Determination of jurisdiction at resolving the disputes, brought by organs of State employment service of Ukraine regarding the compensation of material loss - Берлач, Наталія Анатоліївна; Бучик, Анна Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Actual and debatable problems of ensuring uniformity of judicial practice are expounded in the article, since perfection in realization of principle of legal definiteness ensures forecast of court decisions and stability of the legal regulation. It is marked that the European court on human rights in the legal decisions repeatedly emphasized it, since the principle of legal definiteness is one of the fundamental aspects of supremacy of right. It is indicated that the decisions of the Supreme Court of Ukraine are the source of domestic judicial practice for national courts. As a current legislation does not answer the requirements of precision and unambiguity of legal directions, there is a difficult question of insuring identicalness of application of norms of judicial right. It is investigated, that lately practice of the Higher administrative court of Ukraine in lawsuits of organs of State employment service of Ukraine against juridical and physical persons concerning determination of jurisdiction of the last in relation to a question differs greatly. It is well-proved that deciding a question of attributing a dispute to public-legal general theoretic and legislative criteria should be taken into account. In particular, in public-legal disputes, as a rule, at any rate one side is an body of the executive power, organ of local self-government, their public or official servant or other subject which carries out imperative administrative functions on the basis of legislation, including functions of implementation of the delegated powers. The conclusion is drawn that taking into account a practice of consideration of the Supreme Court of Ukraine in lawsuits of the directly marked category, that are considered to be the public disputes that arise with the participation of the subject of imperative powers, that realizes in disputable legal relationships given to it by a current legislation imperative administrative functions in the field of the public policy of employment of population, there is no reason not to attribute such disputes to the administrative jurisdiction, that is why an initiation of the proceeding in the indicated cases should be carried out according to the rules of administrative law-proceedings.